An unusual cause of fungal pneumonia - S Dharmic; Shraddha Nair; M Harish (Wolters Kluwer Medknow Publications, 2015)
A 65 year old female, known asthmatic on steroids intermittently, with no other co-morbidity presented with fever, breathlessness and cough with mucoid expectoration of ten days duration with bilateral crepts, went for Type II respiratory failure and was intubated followed by tracheostomy in view of prolonged ventilator support. In spite of high end antibiotics as per sputum culture sensitivity, weaning off the ventilator was not possible. Blood investigations revealed leucocytosis with neutrophilic predominance and I g E levels were within normal limits. CT chest showed multiple patchy consolidations of the right upper, middle and lower lobes with ground glass appearance and enlarged mediastinal lymph nodes. Work up for retrovirus, tuberculosis and Sputum for KOH mount was negative. No evidence of sputum and blood eosinophilia. BAL sample grew Curvularia species. Fluconazole 150mg OD was added. Serial imaging of the chest showed resolution of the consolidation and was weaned off the ventilator and was comfortable on room air. Pneumonia caused by Curvularia, in an immune competent patient is very rare. Even in broncho pulmonary involvement these fungi usually occur in allergic conditions as in ABPA than appearing as a solitary cause for lung infection. But if diagnosed and treated early, will respond well to triazoles. This case report highlights a unilateral fungal pneumonia with dramatic clinical improvement post treatment once the rare causative organism was identified.